S˘al˘agean-type harmonic multivalent functions defined by q-difference operator - AHUJA, Om P.; ÇETINKAYA, Asena; Oya MERT, Oya MERT (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
We introduce a new subclass of S˘al˘agean-type harmonic multivalent functions by using q−difference operator. We investigate sufficient coefficient estimates, distortion bounds, extreme points, convolution properties and neighborhood for the functions belonging to this function class. Mathematics Subject Classification (2010): 30C50, 30C99, 81Q99. Received 6 November 2019; Accepted 8 February 2020.